Antibiotic agrochemical treatment reduces endosymbiont infections and alters population dynamics in leafminers, thrips, and parasitoid wasps - Ohata, Yuta; Tagami, Yohsuke (Frontiers in Microbiology, 2025)
IntroductionThe agricultural pests Liriomyza trifolii (Diptera: Agromyzidae) and Hercinothrips femoralis (Thysanoptera: Thripidae) harbor the endosymbiont Wolbachia, which induces cytoplasmic incompatibility and thelytokous parthenogenesis (asexual reproduction of female offspring without fertilization), respectively. The parasitoid Neochrysocharis formosa (Hymenoptera: Eulophidae), a natural enemy of leaf miners, is infected with Rickettsia, which also induces thelytokous parthenogenesis. Although symbionts can be eliminated in laboratory settings using antibiotics mixed with physical manipulation, the effects of agrochemical antibiotics designed for plant disease control on these insects and their symbionts remain unexplored. This study investigated the effects of MycoShield, a commercially available agrochemical containing 17% oxytetracycline, on symbiont-infected populations of these three insect species.MethodsMycoShield was applied to kidney bean plants or mixed into honey to expose L. trifolii, H. femoralis, and N. formosa to oxytetracycline. Offspring were screened for symbiont presence using PCR, and infection frequencies were compared across treatment concentrations. Additionally, H. femoralis populations were monitored in caged conditions under continuous exposure to treated plants.ResultsAt standard concentrations (1,000-fold dilution), MycoShield eliminated Wolbachia from L. trifolii and H. femoralis, resulting in L. trifolii producing uninfected offspring and H. femoralis producing only uninfected males. Similarly, Rickettsia was eliminated from N. formosa when adults ingested MycoShield-mixed honey. Additionally, N. formosa appeared to ingest the antibiotic indirectly by parasitizing L. trifolii larvae that had fed on treated leaves. Symbiont elimination was dose-dependent. Long-term exposure led to a substantial reduction in H. femoralis populations. Two out of eleven cages experienced complete extinction by day 100, likely due to genetic drift resulting from severe reproductive bottlenecks.DiscussionThese findings demonstrate the potential of agrochemical antibiotics such as MycoShield as insecticidal agents targeting symbiont-mediated reproduction, with possible applications in sterile insect techniques. Further research is required to optimize efficacy and assess feasibility under field conditions.